Supplementary Material - Amelia Clark (14918421) (2024)
Supplementary materials provided include the mean radial growth of Pythium ultimum on potato dextrose agar (PDA) and PDA containing fluorescein; a table highlighting the equipment and setting used to obtain microscopy images; images and a graph showing the relative fluorescence intensity of rinsed hyphae compared to unrinsed hyphae grown on PDA with fluorescein; and descriptions of each supplementary video. Supplementary videos are available online.